The Society of Toxicologic Pathology: Advances and Adventures in the First 50 Years. (December 2021) - Hoenerhoff, Mark; Fossey, Stacey; Keenan, Charlotte; Bédard, Agathe; Lejeune, Typhaine; Kerns, William; Patrick, Daniel; Quist, Erin; Bolon, Brad
The Society of Toxicologic Pathology (STP, https://www.toxpath.org /) was founded in North America in 1971 as a nonprofit scientific and educational association to promote the professional practice of pathology as applied to pharmaceutical and environmental safety assessment. In the ensuing 50 years, the STP has become a principal global leader in the field. Society membership has expanded to include toxicologic pathologists and allied scientists (eg, toxicologists, regulatory reviewers) from many nations. In addition to serving membership needs for professional development and networking, major STP outreach activities include production of articles and presentations designed to optimize toxicologic pathology procedures ("best practice" recommendations), communicate core principles of pathology evaluation and interpretation ("points to consider" and "opinion" pieces), and participation in international efforts to harmonize diagnostic nomenclature. The STP has evolved into an essential resource for academic, government, and industrial organizations that employ and educate toxicologic pathologists as well as use toxicologic pathology data across a range of applications from assessing product safety (therapies, foods, etc) to monitoring and maintaining environmental and occupational health. This article recapitulates the important milestones and accomplishments of the STP during its first 50 years.